A facile strategy for fabricating PCL/PEG block copolymer with excellent enzymatic degradation. (June 2017) - Wang, Haipeng; Tong, Dejin; Wang, Lei; Chen, Lei; Yu, Na; Li, Zhanxiong
Abstract: Poly(ω-caprolactone) (PCL) has been the focus in many research initiatives, especially regarding various ways though which to introduce reactive sites to the polyester chains. In this work, hydroxyl groups were covalently introduced into the chain of PCL by reacting ester groups with 6-amino-1-hexanol. Poly(ethylene glycol) (PEG) was crosslinked to the PCL chain through esterification, by using N, N'-carbonyldiimidazole (CDI) as catalyst. The prepared PCL-PEG copolymers were characterized by various analytical techniques such as Fourier transform infrared spectroscopy (FT-IR), 1 H NMR and X-ray photoelectron spectroscopy (XPS). Static water contact angles measurement indicated that hydrophilicity of the copolymer films modified by PEG has improved considerably. The copolymer films were prepared by casting the polymer solution onto a stainless plate. The degradation of the copolymer samples, in a phosphate buffer solution containing a type of Lipase (Aspergillus Oryzae), was observed at different time intervals. The results of weight loss ratio, during the degradation process, indicated that blocking PEG chains onto the PCL chains can effectively accelerate the process of enzymatic degradation of the resulting copolymer. The changes in molecular weight of the copolymer films were investigated by Gel Permeation Chromatography (GPC) and the copolymers were characterized by 1 H NMR during degradation. Surface morphology of PCL and PCL-PEG polymers, before and after degradation, was observed by Scanning electron microscopy (SEM), and emphasized that the enzymatic degradation of PCL-PEG copolymers occurred faster by comparison with PCL, starting from the surface layer of the films.